The Impacts of the COVID-19 Pandemic on HIV Testing Utilization Among Men Who Have Sex With Men in China: Cross-sectional Online Survey - Ke Chun Zhang; Yuan Fang; He Cao; Hongbiao Chen; Tian Hu; Ya Qi Chen; Xiaofeng Zhou; Zixin Wang (JMIR Publications, 2022)
BackgroundThe COVID-19 pandemic has created disruptions in HIV prevention and sexual health services for men who have sex with men (MSM). ObjectiveThis study compared HIV testing utilization in 3 different reference periods (period 1: before the COVID-19 outbreak, November 2019-January 2020; period 2: after the outbreak, February-April 2020; and period 3: after the pandemic was under initial control, May-July 2020). Factors associated with HIV testing utilization after the COVID-19 outbreak (combined periods 2 and 3) were also investigated. MethodsParticipants were MSM aged ≥18 years living in Shenzhen, China. Those self-reporting as HIV positive were excluded. A total of 595 participants recruited through multiple sources completed a self-administered online survey during August-September 2020. HIV testing utilization after the COVID-19 outbreak was the dependent variable, and multivariate logistic regression models were fitted. ResultsHIV testing utilization was significantly lower in period 2 than in period 1 (n=262 vs 363, 44.0% vs 61.0%, P<.001). However, HIV testing utilization was not significantly higher in period 3 than in period 2 (n=277 vs 262, 46.6% vs 44.0%, P=.21). The prevalence of HIV testing utilization after the COVID-19 outbreak was seen in 331 (55.6%) participants. After adjusting for significant background characteristics, condomless anal intercourse (CAI) with regular male sex partners (RPs; adjusted odds ratio [AOR] 2.15, 95% CI 1.29-3.57) and sexualized drug use (SDU; AOR 2.94, 95% CI 1.41-6.06) both before and after the COVID-19 outbreak, CAI with RPs (AOR 2.07, 95% CI 1.06-4.07) and nonregular male sex partners (NRPs; AOR 3.57, 95%CI: 1.43-8.89) only after the COVID-19 outbreak was positively associated with the dependent variable. Regarding HIV prevention service utilization, HIV testing utilization before the COVID-19 outbreak (AOR 10.75, 95% CI 7.22-16.02) and the use of sexually transmitted infection (STI) testing (AOR 7.02, 95% CI 4.10-12.02), other HIV/STI prevention (AOR 3.15, 95% CI 2.16-4.60), and preexposure prophylaxis (PrEP; AOR 3.58, 95% CI 1.54-8.34) after the COVID-19 outbreak were associated with higher HIV testing utilization. The current perceived risk of HIV infection was higher than that before the COVID-19 outbreak (AOR 1.15, 95% CI 1.01-1.30), and perceived COVID-19 preventive measures taken by HIV testing service providers to be effective (AOR 1.52, 95% CI 1.29-1.78) and perceived higher behavioral control to undergo HIV testing (AOR 1.18, 95% CI 1.00-1.40) were positively associated with HIV testing utilization. Concerns about COVID-19 infection during HIV testing (AOR 0.78, 95% CI 0.68-0.89), avoiding crowded places (AOR 0.68, 95% CI 0.48-0.98), and HIV testing service providers reducing their working hours (AOR 0.59, 95% CI 0.48-0.98) were negatively associated with the dependent variable. ConclusionsHIV testing utilization among Chinese MSM declined after the COVID-19 outbreak and did not increase after the pandemic was under initial control. Removing structural barriers to accessing HIV testing caused by COVID-19, modifying perceptions related to HIV testing, and making use of HIV self-testing (HIVST) might be useful strategies to improve HIV testing among MSM during the pandemic.